Spirometric values in high-altitude overweight population - Córdova Córdova, Enrique G. (2018)
Introduction: Spirometry is used to evaluate the respiratory function, relating the spirometric values (VE) obtained with predetermined VE. By recommendation, Peru uses the Mexican American population´s equations to obtain their predetermined VE. The population that live in high altitude have higher VE than the predetermined VE. On the other hand, obese people have alteration in respiratory dynamics. In overweight people who live in high altitude, the changes in their VE are unknown, reason that motivated this research. Objective: To Compare the VE obtained in overweight population that live in high altitude with the VE predetermined by the Mexican American population´s equations. Methods: Descriptive, correlational, retrospective study. We present 329 spirometries (239 males and 90 females), with quality grades A and B, performed in an occupational clinic from Huancayo, between February 2017 and January 2018, in overweight people clinically healthy, with ages between 20 to 40 years old. The VE and the body mass index (BMI) were evaluated, then performing the Spearman and Pearson correlation between them. Results: The average VE obtained were greater than 110% of the predetermined average VE. The Pearson correlation between VE and BMI was negative. Conclusions: The overweight population´s VE that live in high altitude are higher than the predetermined VE, with an inverse relation between VE and BMI.